Examining Test-Retest Reliability and Reliable Change for Cognition Endpoints for the CENTER-TBI Neuropsychological Test Battery - Stenberg, Jonas; Karr, Justin E.; Karlsen, Rune H.; Skandsen, Toril; Silverberg, Noah D.; Iverson, Grant L. (Frontiers in Neurology, 2020)
Objective: Seven candidate cognition composite scores have been developed and evaluated as part of a research program designed to validate a cognition endpoint for traumatic brain injury (TBI) research and clinical trials, but these composites have yet to be examined longitudinally. This study examined test-retest reliability and methods for determining reliable change for these seven candidate composite scores, using the neuropsychological test battery from the Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI). Methods: Participants (18–59 years-old) with mild TBI (n = 124), orthopedic trauma without head injury (n = 67), and healthy community controls (n = 63) from the Trondheim MTBI follow-up study completed the CENTER-TBI neuropsychological test battery at 2 weeks and 3 months after injury. The battery included both traditional paper-and-pencil tests and computerized tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB). Seven composite scores were calculated for the paper-and-pencil tests, the CANTAB tests, and all tests combined (i.e., 21 composites in total on each assessment): the overall test battery mean (OTBM); global deficit score (GDS); neuropsychological deficit score-weighted (NDS-W); low score composite (LSC); and the number of scores ≤5th percentile, ≤16th percentile, or <50th percentile. The OTBM was calculated by averaging T scores for all tests. The other composite scores were deficit-based scores, assigning different weights to low scores. Results: All composites revealed better cognitive performance at the 3-month assessment compared to the 2-week assessment and the magnitude of improvement was similar across groups. Differences, in terms of effect sizes, were largest on the OTBMs. In the combined composites, the test-retest correlation was highest for the OTBM (Spearman's rho = 0.87, in the community control group) and lowest for the number of scores ≤5th percentile (rho = 0.41). Conclusion: The high test-retest reliability of the OTBM appears to favor its use in TBI research; however, future studies are needed to examine these candidate composite scores in participants with more severe TBIs and cognitive deficits and the association of the composites with functional outcomes.